CRISPR for Crop Improvement: An Update Review - Jaganathan, Deepa; Ramasamy, Karthikeyan; Sellamuthu, Gothandapani; Jayabalan, Shilpha; Venkataraman, Gayatri (Frontiers in Plant Science, 2018)
The availability of genome sequences for several crops and advances in genome editing approaches has opened up possibilities to breed for almost any given desirable trait. Advancements in genome editing technologies such as zinc finger nucleases (ZFNs), transcription activator-like effector nucleases (TALENs) has made it possible for molecular biologists to more precisely target any gene of interest. However, these methodologies are expensive and time-consuming as they involve complicated steps that require protein engineering. Unlike first-generation genome editing tools, CRISPR/Cas9 genome editing involves simple designing and cloning methods, with the same Cas9 being potentially available for use with different guide RNAs targeting multiple sites in the genome. After proof-of-concept demonstrations in crop plants involving the primary CRISPR-Cas9 module, several modified Cas9 cassettes have been utilized in crop plants for improving target specificity and reducing off-target cleavage (eg. Nmcas9, Sacas9, Stcas9). Further, the availability of Cas9 enzymes from additional bacterial species has made available options to enhance specificity and efficiency of gene editing methodologies. This review summarizes the options available to plant biotechnologists to bring about crop improvement using CRISPR/Cas9 based genome editing tools and also presents studies where CRISPR/Cas9 has been used for enhancing biotic and abiotic stress tolerance. Application of these techniques will result in the development of non-genetically modified (Non-GMO) crops with the desired trait that can contribute to increased yield potential under biotic and abiotic stress conditions.